Health Behavior and Medication Adherence in Hypertensive Client - Wiwin Wiarsih; Nurul Miftahul Jannah; Junaiti Sahar (GLOBAL HEALTH SCIENCE GROUP, 2020)
Hypertension as Non-Communicable Diseases (NCD) is the largest contributor to the causes of death in the world. Complications of hypertension account for the majority of deaths globally. Uncontrolled health behavior in patients with hypertension is closely related to an increase in morbidity rates due to complications from hypertension each year. Medication adherence is one of an effort to form positive health behaviors to prevent hypertension complications. This study aims to identify the relationship between health behavior with medication adherence in hypertensive clients in Cipayung District, East Jakarta. This study using cross sectional design, approach with 109 participants, who were selected by purposive sampling, are choosen primary hypertensive clients of middle adulthood. The results of the chi square test showed that there was a relationship between health behavior and medication adherence (p value: 0.024) 90% CI. The results of the study it can be concluded that the more positive the health behavior, the higher the adherence to taking medication in hypertensive clients. Community nurses have an important role in modifying the behavior of hypertensive patients with a variety of approaches both as individuals, families, and the public can maintain their health well-being. Keywords: hypertension; health behavior; medication adherence